Climate Change Alters Trophic Interactions in Coastal Ecosystems - Speights, Cori J. (East Carolina University, 2016)
Understanding the effects of multiple anthropogenic changes on local ecosystems is important for understanding community interactions. Because they lie at the interface between the land and sea coastal ecosystems are often heavily impacted by anthropogenic stressors and environmental change. For example, approximately one third of the anthropogenic CO2 released into the atmosphere is taken up by the ocean, causing reductions in pH and in the amount of bio-available carbonate ions. Simultaneously, we are experiencing increases in sea surface temperatures. These two stressors are impacting coastal ecosystems by altering biodiversity, species phenology and distribution, community composition, and biological invasions. These changes in individual species will undoubtedly affect their trophic interactions, which might be especially important for ecological communities centered around foundation species, which stabilize and provide habitat for a multitude species. Therefore, I asked if ocean acidification and increased sea surface temperatures would impact growth and survival of the foundation species, the eastern oyster (Crassostrea virginica), change the nature of the trophic interactions between juvenile eastern oysters and predatory mud crabs (Panopeus spp.), and alter coastal community compositions. To examine these questions I setup a 2x4 experimental design where oysters were grown in one of two levels of CO2 (ambient and elevated) and one of four different temperature treatments (0, 1, 2, and 3[degrees]C above ambient). Oysters alone showed decreased survival, shell height, and filtration with increasing temperature. In the presence of mud crabs, more oysters were consumed when grown in elevated CO2 and increased temperature. Elevated CO2 environments increased soft bodied organisms, such as Molgula manhattensis which can compete with oysters for food and settling space, and decreased the presence of organisms that rely on calcium ions. These results illustrate the importance of investigating trophic interactions in multiple stressor environments. These types of studies are an important step for managers attempting to understand and predict the impacts of climate change on important and in some cases economically valuable ecosystems.
Keywords: trophic interactions; coastal ecosystems; CO2; temperature; Climatic changes; Biotic communities; American oyster; Scylla (Crustacea); Ocean acidification